Analysis on the ecosystem service protection effect of national nature reserve in Qinghai-Tibetan Plateau from weight perspective. (September 2022) - Zhang, Xiaoyao; Li, Sisi; Yu, Hu
Highlights: Exploring the protection effect of national nature reserve based on ESFs analysis. Comparisons include type and location differences in conservation effectiveness. The establishment of nature reserve caused the spillover of human activities inside. Policy changes have dynamic effects on regional ecosystem service trade-offs. Abstract: The analysis of the protection effect from the perspective of ecosystem service function (ESF) is an important basis for proposing optimal management strategies in nature reserves. Aiming at the internal, external, and different types of nature reserves of the National Nature Reserve in the Qinghai-Tibetan Plateau from 1992 to 2015, this study used the InVEST model to analyze the dynamic changes in four key ESFs, including carbon storage, water conservation, soil retention, and habitat quality. Based on this, the protective effect of nature reserves was evaluated. The main conclusions were as follows: (1) From 1992 to 2015, the spatial distribution pattern of carbon storage, water conservation, soil retention, and habitat quality inside and outside National Nature Reserve in Qinghai-Tibetan Plateau is "high in the east and decreasing to low in the west". On the time scale, the stability inside the reserve was higher than that outside. (2) Among all types of nature reserves, the ESF of forest ecosystem nature reserves always ranked highest, and the ESF of desert ecosystem nature reserves ranked lowest. (3) During the 23-year period, the protection effect of ecosystem services inside National Nature Reserve was between 1.0821 and 1.0870, which was always higher than that of the outside areas. (4) The protection effect of the comprehensive ESF in forest ecosystem nature reserves ranked highest with a value of 1.3169. Although the protection effect of desert ecosystems is relatively weak, it has continuously increased from 0.8836 to 0.8955 over the 23-year period. Based on the changes in the ecological processes of nature reserves, exploring their protection effectiveness will help strengthen the comprehensive understanding of ecosystems in conservation research. The development of effective policies and management measures has had a positive effect on the adaptive adjustment of ecosystem service trade-offs.